Adoption of ex-ante tool to assess environmental impacts of livestock value chains has led to positive changes in knowledge and attitudes about the environmental footprint of livestock production in data-scarce regions - CGIAR Research Program on Livestock (2021)
The CLEANED (Comprehensive Livestock Environmental Assessment for improved Nutrition, a secured Environment and sustainable Development along livestock value chains) ex-ante tool was developed to assess the environmental impacts of livestock systems. Numerous trainings and workshops have been conducted to teach end users (e.g. researchers, livestock industry stakeholders, educators, and policymakers) how to use it effectively, leading to positive changes in knowledge and attitudes about the environmental impact of livestock production in data scarce environments throughout Africa, Asia, and Latin America.